Sudden Death and Coronary Artery Anomalies - Rizzo, Stefania; De Gaspari, Monica; Frescura, Carla; Padalino, Massimo; Thiene, Gaetano; Basso, Cristina (Frontiers in Cardiovascular Medicine, 2021)
Congenital coronary artery anomalies (CAA) include a wide spectrum of malformations present at birth with various clinical manifestations and degrees of severity. Patients may be asymptomatic, and CAA are an incidental finding during coronary angiography or at autopsy. However, in other cases, ischemia-related signs and symptoms and arrhythmias leading to an increased risk of sudden cardiac death (SCD), often as the first presentation of the disease, may occur. In this chapter, we discuss the normal origin and course of the coronary arteries (CA) and the pathology of CAA at risk of SCD, including our experience with victims of SCD among young population (ages <40 years) and athletes.